THE INFLUENCE OF GADGETS ON THE SOCIAL BEHAVIOR OF STUDENTS AT MTS TARBIYATUL ISLAMIYAH SOKOPULUHAN PUCAKWANGI PATI - Nurul Hidayah; Rofiq Faudy Akbar (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2024)
This research aims to investigate the intensity of gadget usage, the social behavior of students, and the influence of gadgets on the social behavior of students at MTs Tarbiyatul Islamiyah. The method employed is quantitative, with a non-experimental approach and the use of simple random sampling technique. The sample size consists of 75 respondents, and data collection is conducted through questionnaires. The results of this indicate that the data on gadget usage intensity yield percentages of 42% for respondents answering